Indonesia : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report, 2018)
This 2017 Article IV Consultation highlights that the Indonesian economy has continued to perform well. The economic outlook is positive. Real GDP growth is projected at 5.1 percent in 2017, rising gradually to 5.6 percent over the medium term, led by robust domestic demand. Inflation is projected to remain about 3.5 percent, within the official target range, owing to stable food and administered prices, and well anchored inflation expectations. The current account deficit is expected to remain contained at near 2 percent of GDP owing to firm commodity prices and robust exports. Risks to the outlook remain tilted to the downside, including spikes in global financial volatility, uncertainty around the United States economic policies, lower growth in China, and geopolitical tensions.